Green Synthesis of ZnO Nanoparticles using Aloe Vera Extract and Xanthan Gum as Modifier for Photocatalytic Degradation of Anionic and Cationic Dye in Aqueous Solution - Imelda Fajriati; Priyagung Dhemi Widiakongko; Didik Krisdiyanto; Heti Hermawati (Bulletin of Chemical Reaction Engineering & Catalysis, 2026)
The green synthesis of Zinc Oxide (ZnO) nanoparticles is a simpler, low-energy method that avoids toxic chemicals, making the process more cost-effective and environmentally friendly. The green synthesis was performed using aloe vera extract (55% - Aloin), rich in electrons from its hydroxyl groups, as a reducing agent, and natural polysaccharides from xanthan gum to disperse particles and prevent agglomeration. The green synthesis product was characterized using scanning electron microscopy, Fourier Transform spectroscopy, X-ray diffraction, transmission electron microscopy, and Diffuse Reflectance UV spectroscopy. The green-synthesized ZnO nanoparticles, both with xanthan gum (ZnO-AL/XG) and without xanthan gum (ZnO-AL), adopted a hexagonal wurtzite crystal structure. The addition of xanthan gum significantly reduced the crystallite size and enhanced the surface homogeneity of the photocatalyst. Over 50% removal of both anionic and cationic dyes was achieved by ZnO-AL/XG for up to 3 uses, and by ZnO-AL for up to 2 uses, respectively. These findings highlight the potential of the aloe vera–xanthan gum-based green synthesis as a sustainable and efficient strategy for producing ZnO nanomaterials applicable in dye wastewater treatment. Copyright © 2026 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).